Hubungan Pengetahuan Ibu Tentang Imunisasi Dengan Pemberian Imunisasi Dasar Lengkap Pada Bayi Di Puskesmas Penanggalan Kecamatan Penanggalan Kota Subulussalam Tahun 2023 - Sonia Novita Sari; Tri Sumarsih; Sarifin Usman Kombih; Imarina Tarigan (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Immunization is an effort to actively create/increase a person's immunity against a particular disease, so that if one day they are exposed to that disease they will not get sick or will only experience mild illness. The aim of this research is to determine the relationship between maternal knowledge about immunization and providing complete basic immunization to babies at the Penanggalan Community Health Center, Penanggalan District, Subulussalam City. Quantitative design using cross sectional. The population in this study were mothers who had children or babies aged 10-12 months, namely 40 respondents. Data analysis uses univariate, bivariate analysis. The results of this study show that there is a relationship between maternal knowledge about immunization and the provision of complete basic immunization to babies at the Penanggalan Public Health Center, Penanggalan District, Subulussalam City in 2023. Suggestions are given for research and for research sites and for educational institutions regarding complete basic immunization in babies.